Exercise-based interventions for preventing and treating cancer therapy-related cardiovascular toxicity: a systematic review and meta-analysis - Qun Wang; Zehao Huang; Sek Ying Chair (BMC Cardiovascular Disorders)
Abstract Purpose This review aimed to evaluate the effects of exercise-based interventions on cancer therapy-related cardiovascular toxicity (CTR-CVT) in individuals with cancer. Methods Four databases (MEDLINE, Embase, Web of Science, and CENTRAL) were searched to identify eligible studies. Randomized controlled trials examining the effects of exercise-based interventions on CTR-CVT in cancer patients published in English were included. The risk of bias of included studies was assessed using version 2 of the Cochrane risk-of-bias tool for randomized trials. The meta-analysis was performed using statistical software R. The PRISMA statement was followed. Results Thirty studies with 2484 participants were included. Our findings revealed that compared to the control group, exercise-based intervention improved VO2peak (mean difference [MD]: 1.62, 95% confidence interval [CI]: 0.94 to 2.30), resting diastolic blood pressure (MD: -4.43, 95% CI: -8.72 to -0.13), and resting heart rate (MD=-3.74, 95% CI: -6.59, -0.89) among individuals with cancer. Evidence on other study outcomes remains unclear. Conclusion The findings of this review demonstrate the potential role of exercises in preventing and treating CTR-CVT. Further research is warranted to strengthen the current evidence and fill the gaps identified in this review. Registration The review protocol was registered in PROSPERO (ID: CRD42022380550).